2018
DOI: 10.14423/smj.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Personalized Health Planning and Shared Medical Appointments for Patients with Type 2 Diabetes Mellitus

Abstract: resident Obama's Precision Medicine Initiative has refocused national attention on the ability of genomics and other emerging technologies to provide a better understanding of the relationship between genetics, environment, lifestyles, and the development of disease 1. This initiative was heralded as a "bold new research effort to revolutionize how to improve health and treat disease" 2. Yet, in 2000 the sequencing of the human genome was also anticipated to lead to new ways to personalize medicine and to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…Some participants have also mentioned that the GMAs increased their personal accountability to attend their appointments. A similar finding was reported in another qualitative study 23 of GMAs in the United States. In addition, Thompson-Lastad 24 reported that staff involved with group medical appointments felt that patient interactions with other patients was the most important aspect of these appointments; they also reported that patients could support one another in ways that health providers could not.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some participants have also mentioned that the GMAs increased their personal accountability to attend their appointments. A similar finding was reported in another qualitative study 23 of GMAs in the United States. In addition, Thompson-Lastad 24 reported that staff involved with group medical appointments felt that patient interactions with other patients was the most important aspect of these appointments; they also reported that patients could support one another in ways that health providers could not.…”
Section: Discussionsupporting
confidence: 90%
“…20 Although GMAs have shown benefits, understanding patient experiences with these types of appointments is essential to help to refine this emerging approach to care for people with type 2 diabetes. Although a few studies to date have captured qualitative patient experiences and perspectives with this method for managing type 2 diabetes, 7,21,23,24 these type of data are scarce. To our knowledge, no studies have examined naturalistic patient experiences and perspectives of GMAs for type 2 diabetes in a rural Saskatchewan context.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of the included studies was generally high; most papers met the majority of the CASP checklist criteria (online supplemental file 2). Weaknesses commonly related to lack of information about participant recruitment [16][17][18][19][20][21][22] and researcher reflexivity, which was missing in all but two studies. 23 24 Figure 1 Flow diagram of review search.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…16 18 19 21 24 25 27-31 Fewer studies captured the views of healthcare managers, programme/research coordinators and administrators. 18 21 23 28-31 The SMAs varied in terms of content, duration, numbers of attendees and frequency of sessions. The majority of studies focused on single-condition SMAs (n=12); three reported on both single-condition and mixed-condition SMAs 29 31 32 ; two reported on mixed-condition SMAs only 27 33 ; and one gave no details.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation